Deeper than the ocean : a novel - Ojito, Mirta A. (Union Square & Co., 2025)
"One hundred years after the shipwreck of the Valbanera, known tohistory as the 'poor man's Titanic,' Mara Denis gets an assignment to report on the Canary Islands, where her ancestors lived before they moved to Cuba. Unexpectedly, she discovers that the grandmother her mother cherished was listed among the dead of the Valbanera, years before Mara's mother was even born. This fateful twist changes everything Mara thought she knew about her family and herself, and sends her on a quest to find the truth. If her great grandmother is a ghost, who is she and where did she come from?"--